Dissimilar gene repertoires of Dickeya solani involved in the colonization of lesions and roots of Solanum tuberosum - Robic, Kévin; Munier, Euphrasie; Effantin, Géraldine; Lachat, Joy; Naquin, Delphine; Gueguen, Erwan; Faure, Denis (Frontiers in Plant Science, 2023)
Dickeya and Pectobacterium species are necrotrophic pathogens that macerate stems (blackleg disease) and tubers (soft rot disease) of Solanum tuberosum. They proliferate by exploiting plant cell remains. They also colonize roots, even if no symptoms are observed. The genes involved in pre-symptomatic root colonization are poorly understood. Here, transposon-sequencing (Tn-seq) analysis of Dickeya solani living in macerated tissues revealed 126 genes important for competitive colonization of tuber lesions and 207 for stem lesions, including 96 genes common to both conditions. Common genes included acr genes involved in the detoxification of plant defense phytoalexins and kduD, kduI, eda (=kdgA), gudD, garK, garL, and garR genes involved in the assimilation of pectin and galactarate. In root colonization, Tn-seq highlighted 83 genes, all different from those in stem and tuber lesion conditions. They encode the exploitation of organic and mineral nutrients (dpp, ddp, dctA, and pst) including glucuronate (kdgK and yeiQ) and synthesis of metabolites: cellulose (celY and bcs), aryl polyene (ape), and oocydin (ooc). We constructed in-frame deletion mutants of bcsA, ddpA, apeH, and pstA genes. All mutants were virulent in stem infection assays, but they were impaired in the competitive colonization of roots. In addition, the ΔpstA mutant was impaired in its capacity to colonize progeny tubers. Overall, this work distinguished two metabolic networks supporting either an oligotrophic lifestyle on roots or a copiotrophic lifestyle in lesions. This work revealed novel traits and pathways important for understanding how the D. solani pathogen efficiently survives on roots, persists in the environment, and colonizes progeny tubers.